Enhancing Children's Creativity Through Art-Craft Training: Peningkatan Kreativitas Anak Melalui Pelatihan Seni Kriya - Deddy Suprapto; Sokema Yeni Astuti; Rara Mustika Ningrum; Fina Zahra (KHD Production, 2025)
Developing creativity in elementary school children is a crucial investment in developing individuals who are not only academically competent but also adaptive and innovative in the future. Crafts, particularly the creation of works from recycled materials such as used bottles, serve as an effective medium for nurturing children's creativity by engaging them in transforming waste into functional and aesthetic visual representations. This process not only improves motor skills but also stimulates holistic cognitive, affective, and psychomotor development, while fostering environmental awareness.This community service activity aimed to enhance the creativity of elementary school children through recycling-based art craft training. The training was conducted for two days at SDN 4 Kebonsari, Kebonsari District, Jember Regency, involving 30 students from grades 4-6. The method used was educative-participatory, focusing on idea exploration and art creation from used bottles. Evaluation was carried out using an assessment rubric measuring four aspects of creativity: fluency, flexibility, originality, and elaboration. The results showed a significant increase in all aspects, with the highest average increase in flexibility. This activity also increased children's intrinsic motivation to create and awareness of the importance of recycling. Recycling-based art craft training is effective as a medium for stimulating the creativity of elementary school children.